" Forecasting Future Cash Flows Using the Metrics of Cash Flow and the Accounting Return " - يحيى, عباس حميد; عبد الرزاق, عمار لؤي (Journal of Economics and Administrative Sciences, 2018)
Providing useful information in estimating the amount and timing and the degree of uncertainty concerning the future cash flows is one of the three main objectives of the financial reporting system, which is done through the main financial statements. The interest on standard-setting bodies in the forecasting of future cash flows, especially Financial Accounting Standards Board (FASB) explain under Accounting Standard (1) of the year 1978 "Objectives of Financial Reporting by Business Enterprises", paragraph (37) thereof that accounting profits better than cash flows when forecasting future cash flows, In contrast, IAS (7) as amended in 1992 aims to compel economic units to prepare statement of cash flows, because the information related to the cash flows for any economic unit useful in providing users of financial statements necessary basis to measure the ability of the unit to generate cash or cash equivalents, and the needs of the unit for the use and benefit of those cash flows.At the level of the Iraqi environment, there is no indication to the economic units work forecasts cash flows, as the decisions made by whether decisions to grant credit or investment decisions are often based on personal experience for managers and decision makers in banks. This research aims to provide an indication (or indicators) from the heart of the financial statements (specifically income statement and statement of cash flows) from which to forecasting extent positive or negative future cash flows of  a particular economic unit, and this index is available to all interested parties, whether the same economic units or current and potential customers with these units.